The Cancellation Of The Conversion Of Lpg Gas Stoves To Electricity In The Framework Of The Role Of The Market And Government In The Islamic Economy - Misi Anggraini; Rozalinda Rozalinda; Ahmad Wira (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The energy requirements for cooking have evolved in the process, namely initially using firewood, then evolving to using kerosene as fuel, and finally using clean technology using Liquefied Petroleum Gas (LPG). From the 2019 APBN, LPG subsidies for 3 KG (Kilo Gram) cylinders are estimated to cost more than $4.9 billion in 2019. The implementation of the Electrification program for various sectors is a demand driven effort to absorb excess capacity of electricity which is underutilized, the current condition of PLN's reserve margin is 15.6%. Apart from that, one of the commitments to achieve NZE in 2060 regarding demand in the 2021-2025 program is a strategy to reduce imports of LPG with electric stoves for 8.2 million households. This research uses a qualitative approach, with problem studies because this method is considered to be the perfect reality methodology for conducting research related to using community participation, as well as interview data collection techniques, observation and secondary data collection. The research results show that the canceled LPG Gas Stove Conversion to Electricity program could not function properly due to lack of political outreach, weak regulations, the strength of the target people and the poor quality of human resources.